Letter - Halifax, Edward Frederick Lindley Wood, Earl of, 1881-1959
027-0061-001 Foreign Office, S.W.1. 7th October, 1939. Dear Sir Walter, I write to acknowledge the receipt of your letter of the 28th September in which you enclosed the sum of £30 for transmission to the family of Senor [Pascual] Tomas in Valencia. 2. Since I undertook to arrange for the transmission of funds to Senor Tomas' family, the Exchange Control Regulations have, as you know, been introduced and consultation with the Treasury is therefore necessary. 3. I will write to you again as soon as possible. Y. sincerely Halifax WJB Sir Walter Citrine, K.B.E. 292/946/27/61